On the growth rate of generalized Fibonacci numbers - Fishkind Donniell E (Advances in Difference Equations, 2004)
Let α(t) be the limiting ratio of the generalized Fibonacci numbers produced by summing along lines of slope t through the natural arrayal of Pascal's triangle. We prove that is an even function.